Mismatch antara Bidang Pendidikan dan Pekerjaan Tidak Selamanya Merugikan: Studi Empiris tentang Kesenjangan Upah Lulusan SMK - Desvira, Tetri; N, Zulkifli (Jurnal Informatika Ekonomi Bisnis, 2025)
This study analyzes wage differentials between vocational high school graduates in Indonesia who work in jobs aligned with their field of training and those who work outside their field, using data from the 2024 National Labor Force Survey. The analytical methods include the Heckman two-step selection model to correct for labor force participation bias, separate OLS regressions for each group, and the Blinder-Oaxaca decomposition to identify the sources of wage disparities. The results show that horizontal mismatch has significant implications for wage structures. Although the average wage difference between matched and mismatched groups is not statistically significant, the decomposition analysis reveals that most of the wage gap arises from differences in observable characteristics, along with a significant influence of unobserved factors (unexplained). These findings suggest that vocational mismatch affects not only labor market efficiency but also wage distribution, which should be taken into account in vocational education and employment policy design.